A. K. Kazembek and the Formation of the Faculty of Asian and African Studies of St. Petersburg University Based on Material from V. V. Bartold and I. Y. Krachkovsky - Eray Akçay (Türkiyat Mecmuası)
Alexander Kasimovich Kazembek (1802-1870) is one of the most important figures in the history of Russian Oriental Studies of the 19th century. He entered the annals of St. Petersburg University primarily as the first dean of the Faculty of Oriental Languages inaugurated in 1855, where he was listed as a professor in the Department of Arabic Studies. Without a shadow of a doubt, this first dean of the Faculty of Oriental Languages left behind his own school of thought called the Kazembek tradition, with his subsequent students achieving breakthroughs in their fields. Vasily Vladimirovich Bartold summarized Kazembek’s importance, saying, “Senkovsky and Kazembek created Russian Orientalism with their lectures; almost all Russian Orientalists of the next generations were students of one of these two scholars or students of their students.” In this context, the article focuses on the founding of the Faculty of Oriental Languages at St. Petersburg University and its first dean, Alexander Kasimovich Kazembek. The article also examines Kazembek’s perspective as an Orientalist, prominent researcher, and teacher of languages and history of the Islamic world regarding the educational curriculum of the Faculty of Oriental Languages in light of the archival documents of two Russian academicians: Vasily Vladimirovich Bartold (1869-1930) and Ignaty Yulianovich Krachkovsky (1883-1951).